ANALISA PERTANGGUNG JAWABAN PENYIDIK POLRI TERHADAP TERJADINYA SALAH TANGKAP ATAU ERROR IN PERSONA - Arinatha Fardian (Universitas 17 Agustus 1945 Samarinda, 2014)
ABTRACTIndonesian National Police is one of the law enforcement agency responsible for performing preventive measures against crime and provide protection to the whole community. In the implementation of criminal law and criminal procedure investigations conducted by the police action as a first step in the process of law enforcement. Dikemukan problems in this thesis is how the duties and functions of the Police in law enforcement, irregularities committed by law enforcement officers as well as how Accountability Investigator Police against the occurrence of false arrest or error in persona.The method used is a normative juridical research. Normative juridical research is research using library materials or secondary data obtained from the literature, Legislation and analyzing and interviewing the relevant government agencies that can help solve the problems in this thesis.Investigators as one of the law enforcement officers are given the authority to enforce the law, therefore the duty and authority should be implemented in accordance with the purpose of establishing the law enforcement agencies and is responsible for the implementation does.Based on the research results obtained by the authors in Kutai Police concluded, investigators in performing its duties and authorities sometimes deviations and errors such as abuse of authority or negligence, as in the case of the investigation, may result in a false arrest by the investigator. Perverts and errors or omissions that may occur due to several factors, including the lack of morality and knowledge in law enforcement investigators. In its duties and powers investigators did not investigate professionally and for negligence or breach of which resulted in one arrest and harming a person or victim, the investigator who commits an offense shall be liable in the event of false arrest or error in persona for committing violations of the Code of Professional Ethics of Police, violation of the Code of Professional Ethics of Police shall be penalized in accordance with the violations committed offenders Keywords : Investigator, Investigation, Police